[Map of sledge journeys and searches of Franklin Search Party of 1878, 79, 80 drawn by H.W. Klutschak] - Klutschak, Heinrich; (1880)
Title provided by cataloger to match the title of the map after published in the AGS of NY journal.; Original manuscript maps Illustrating the Schwatka Expedition in search of Franklin artifacts drawn for the American Geographical Society bearing the initials of expedition member Heinrich Wenzel Klutschak. The map provides an accounting of the movements of the Schwatka expedition (1879-1880), in its search for the papers and other artifacts of Sir John Franklin, which remained in the Arctic Region after his ill-fated attempt to find the Northwest Passage. Based upon a comparison of this map and the printed map which accompanied the American Geographical Society Journal's report of the expedition, it is clear that these two maps were drawn either at the tail end of the Schwatka expedition by Klutschak or under his supervision (each bears his initials), or as part of the preparation of the report published by the AGS.; Later published by the AGS of New York to accompany article pages 237-274 from Journal of the American Geographical Society of New York, vol. XII 1880: "Arctic meeting at Chickering Hall, October 28th, 1880. Reception of Lieut. Frederick Schwatka and his associates of the Franklin Search Party of 1878, 1879 and 1880. Addresses by Chief-Justice Daly, Lieut. Frederick Schwatka, U.S. Army and Dr. Isaac I. Hayes."; "H.W.K." -- lower left corner Grayscale; 1:670,000